Research on the Application of Computer-Aided Software in Interior Design. Issue 1 (April 2021) - Yi, Lu
Abstract: Computer network technology brings people a cross-epoch change. The computer has changed from a behemoth to a small object that is now easy to carry; from the beginning, the computer can only be used for computing, and now it can search for all kinds of information in the network, not only to calculate any questions, but also to shop directly on the Internet. The development of computer technology also promotes the continuous updating of computer aided software. It is because of the emergence of computer-aided software that the traditional way of interior design has changed obviously. Computer aided design makes interior design more convenient and fast. This paper introduces several common computer-aided software and analyzes the application research measures of computer-aided software in interior design.